The Descriptive Analysis of British Accents in Harry Potter and The Philosopher's Stone Film - Zahrotul Ula (Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Kadiri, 2021)
British accent is an accent commonlyspoken by the people from the United Kingdom (UK) that has several kinds. Harry Potter and the Philospher’s Stone is famous film starred by the British actors who use different kinds of British accent. This research is aimed to find out the dominant British accent used by Harry Potter, Ron Weasley, and Hermione Granger who will be later called The Trio, and the students’ perception of British accentspoken in the film to help them learn English. The data was collected by analysing the British accent in the film, and a follow up interview was then conducted and analysed qualitatively. The respondents of this research were four students who have already watched the film. Meanwhile, the instruments to collect the data are the film, the dialog transcripts, an article from Accent Bias Britain, and the interview guide. To validate the data, the researcher asked two validators who have experience in British accent. The research reveals that Harry and Hermione used Received Pronunciation while Ron spoke in Estuary English. The students’ perceptions show that the British accent in this film is pronounced in clear and clean manner so the students found it easy and helpful. Thus, this film is recommended to learn English, especially British accent. Key words : British accent, Harry Potter and The Philosopher’s Stone film, perception, RP, Estuary English